Building Students’ Growth Mindset through Artificial Intelligence Integration in Classroom Learning - Iswahyudi, Miftah; Risti, Syahda Mufida; Fadilla, Vicha Zalfa; Arif, Dikdik Baehaqi (The Indonesian Institute of Science and Technology Research, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed the educational landscape, offering new opportunities to enhance teaching and learning processes. However, the integration of AI in education raises concerns regarding students’ dependency on technology and potential decline in critical thinking skills. Therefore, fostering a growth mindset among students becomes essential to ensure that AI serves as a learning support tool rather than a substitute for cognitive effort. This article explores how AI integration in classroom learning can promote students’ growth mindset, critical thinking, and problem-solving abilities. The study adopts a qualitative conceptual analysis supported by recent empirical literature on AI in education and growth mindset theory. The proposed framework examines the relationship between AI-supported learning, pedagogical strategies, and student mindset development. The findings indicate that AI can positively contribute to the development of a growth mindset when teachers implement strategies such as exploratory learning, reflective practices, project-based learning, digital ethics instruction, and process-oriented feedback. The results further show that AI-enhanced learning environments can encourage deeper engagement, creativity, and collaborative learning if accompanied by appropriate pedagogical guidance. However, challenges such as digital literacy gaps, ethical concerns, and overreliance on AI must be addressed through effective instructional design and policy frameworks. This study contributes to the growing discourse on AI in education by proposing a practical pedagogical model that integrates AI technologies with growth mindset principles to foster resilient and adaptive learners in the digital era.